ChemInform Abstract: Oxone‐Mediated Facile Access to Substituted Pyrazoles. Issue 20 (April 2016) - Kashiwa, Mitsuhiro; Kuwata, Yoshiyuki; Sonoda, Motohiro; Tanimori, Shinji
Abstract: Starting from easily accessible hydrazones, aryl‐ and alkyl‐ substituted pyrazoles are prepared.